Performance Analysis of various dc-link Converters for Photovoltaic based Ac Drives - Sanket, B; Pandian, A; V. Siva Reddy, K (International Journal of Engineering & Technology, 2018)
This paper proposes a Performance analysis of DC to DC converters connected to the induction motor drive. The circuit analysis and operating principle of the proposed M-ZS Converter is presented and also characteristics of the different DC-DC are projected. A keen comparison is done between the proposed Modified Z-Source Converter with Boost Converter and Z-Source Converter and MPPT behavior of three converters at different irradiance level and different loading conditions are analyzed. By with the help of MATLAB Simulink, the simulation results are evaluated and presented.Â